Examining External Dose Rates in Mamuju Regency, Indonesia: A Personal Radiation Dosimetry Approach - Rakotovao Lovanantenaina Omega; Adi R.A. Abdullah; Sidik Permana; Wahyu Srigutomo; Alan Maulana; Haryo Seno; Ismail Humolungo; Fungki Iqlima Nasyidiyah; Zulfahmi Zulfahmi; Frafti Rejeki; Rahmi Elzufiah (Journal of Engineering and Technological Sciences, 2023)
This study aimed to quantify the individual external radiation exposure in Mamuju, Indonesia. A SmartRad portable personal dosimeter was utilized for this purpose, and data was collected over a period of 30 days. The findings indicate that the dose rate varies from 0.152 to 4.200 μSv/h and cumulatively ranges from 0.1 to 8.4 μSv/day based on an average measurement duration of 160 minutes. The average dose rate in areas with mineral deposits is 11.02 mSv per year. In contrast, the average effective dose in areas without radioactive mineral deposits is 2.6493 mSv per year. The annual average effective dose for individuals was measured at 6.8347 mSv. These findings imply that personal exposure to radiation among the public in Mamuju exceeds the threshold recommended by the International Commission of Radiological Protection.